CHALLENGES OF INDONESIAN CONTRACT LAW IN THE DIGITAL BUSINESS ERA - Rohaya, Nizla; Sinulingga, Dini Bahraini; Mutiara, Upik (Universitas Muhammadiyah Sumatera Barat, 2023)
This research is motivated by the author's interest in observing the development of Indonesian contract law which until now continues to face challenges, especially in the era of globalization where there has been a shift in business activities from conventional to digital era. The purpose of this study is to analyze the readiness of Indonesian contract law in the face of its increasingly diverse developments that affect social aspects and change the way business people interact with each other. The transaction process in the business world that is carried out without direct meetings using internet media is included in the category of electronic transactions. Electronic transactions in business have various forms, one of which is electronic commerce or commonly known as e-commerce. This advancement makes it easier for individuals and companies to carry out various types of business transactions, especially in trade. This research uses normative legal research method through conceptual approach. The results show that there are several issues that are still a problem for Indonesian contract law, one of which is the validity of electronic contracts and dispute resolution in online transactions. In answering this issue, the author urges the government to immediately create and pass a new contract law, namely the National Contract Law which, as of this writing, is still in the drafting stage.